Molecular interactions of the tyrosine kinase ZAP-70 in T cells - Rhoda, Donita Jean (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.M.S. (Medical Biochemistry)) -- University of Stellenbosch, 1997.